2002
DOI: 10.1046/j.1439-0507.2002.00709.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of systemicCandidainfections in patients of the intensive care unit. Significance of serum antigens and antibodies

Abstract: The combined detection of Candida antigen and antibody for the determination of systemic Candida infections (SCI) was investigated. One hundred and four patients from the intensive care unit (ICU) were analysed. Seventeen of the patients were suspected of having SCI, based on clinical and laboratory criteria. In these patients, Candida antigens and antibodies were analysed extensively. Ten patients had a positive Candida antigen (titre >1:16) determined by the latex agglutination assay Cand-Tec(R) and their me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The laboratory diagnosis of candidaemia is presently based on direct examination and conventional blood culture with a sensitivity of only 40%. 2 Microbiological evidence for the diagnosis of invasive candidiasis requires multiple consecutive blood cultures. The current phage-ELISA demonstrated that 77% of mice with systemic C. albicans infection produced 1 The specimens were obtained from mice (n ¼ 30) infected intravenously with 10 6 C. albicans strain ATCC 10231.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The laboratory diagnosis of candidaemia is presently based on direct examination and conventional blood culture with a sensitivity of only 40%. 2 Microbiological evidence for the diagnosis of invasive candidiasis requires multiple consecutive blood cultures. The current phage-ELISA demonstrated that 77% of mice with systemic C. albicans infection produced 1 The specimens were obtained from mice (n ¼ 30) infected intravenously with 10 6 C. albicans strain ATCC 10231.…”
Section: Discussionmentioning
confidence: 99%
“…The current phage-ELISA demonstrated that 77% of mice with systemic C. albicans infection produced 1 The specimens were obtained from mice (n ¼ 30) infected intravenously with 10 6 C. albicans strain ATCC 10231. 2 Using 50 ll of blood collected. 3 Positive results were determined according to Table 1: OD of serum ‡0.159 (mean OD + 2 SD of non-infected control group).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…those with diabetes mellitus and those undergoing immunosuppressive therapy, fungi can cause a variety of opportunistic infections (11). Candida species, in particular, are implicated in nosocomial infections (4, 22). Therefore, fungal infections are sometimes referred to as ‘diseases of the diseased’ (26).…”
mentioning
confidence: 99%